1991
DOI: 10.1089/lps.1991.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hypothermia

Abstract: Operative laparoscopy is experiencing an increase in its use and indications. This expansion exposes patients to increased operating time, larger volumes of carbon dioxide for maintenance of a pneumoperitoneum, and higher gas flow rates for intraperitoneal delivery. Patients with medical complications, advancing age, and potentially contaminated procedures are now considered acceptable candidates for operative endoscopic techniques via laparoscopy. A previously observed but unquantified amount of hypothermia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 4 publications
2
47
1
3
Order By: Relevance
“…They have suggested that: a) the tissue trauma in the form of intraperitoneal manipulations-pulling of the gallbladder and mesentery-are similar in both methods 17 and b) the pneumoperitoneum is an aggravating factor on the surgical wound, because: 1) it causes acute dilatation of the peritoneum and irritation of the peritoneal nerve endings that activates receptors, permanent pressure on the diaphragm during surgery, CO2 absorption by the peritoneum, increased partial pressure in the blood and respiratory acidosis 17,18 and 2) the commercial CO2 used for creating the pneumoperitoneum is fluid and changes into its gaseous form at its boiling point of 21.1°C. 19 Thus, its prolonged use might cause a drop in body temperature, even though this is at least partially avoided by heating it at 30 to 30.5°C. 20 Other studies have suggested the effect of the pneumoperitoneum is not a major wound-aggravating factor because: a) a significant increase in CO2 and respiratory acidosis in laparoscopic cholecystectomy is observed only in patients with chronic cardiopulmonary failure and preoperative restrictive lung function, [21][22][23][24] b) with increasing surgical experience, the pneumoperitoneum is sufficient even at smaller pressures, 1,4,6 and c) the duration of surgery is now considerably briefer than that described in the earlier series.…”
Section: Discussionmentioning
confidence: 99%
“…They have suggested that: a) the tissue trauma in the form of intraperitoneal manipulations-pulling of the gallbladder and mesentery-are similar in both methods 17 and b) the pneumoperitoneum is an aggravating factor on the surgical wound, because: 1) it causes acute dilatation of the peritoneum and irritation of the peritoneal nerve endings that activates receptors, permanent pressure on the diaphragm during surgery, CO2 absorption by the peritoneum, increased partial pressure in the blood and respiratory acidosis 17,18 and 2) the commercial CO2 used for creating the pneumoperitoneum is fluid and changes into its gaseous form at its boiling point of 21.1°C. 19 Thus, its prolonged use might cause a drop in body temperature, even though this is at least partially avoided by heating it at 30 to 30.5°C. 20 Other studies have suggested the effect of the pneumoperitoneum is not a major wound-aggravating factor because: a) a significant increase in CO2 and respiratory acidosis in laparoscopic cholecystectomy is observed only in patients with chronic cardiopulmonary failure and preoperative restrictive lung function, [21][22][23][24] b) with increasing surgical experience, the pneumoperitoneum is sufficient even at smaller pressures, 1,4,6 and c) the duration of surgery is now considerably briefer than that described in the earlier series.…”
Section: Discussionmentioning
confidence: 99%
“…A videolaparoscopia é um procedimento cada vez mais utilizado e indicado [14][15][16] . Várias pesquisas têm procurado avaliar seu efeito na formação de aderências e no desenvolvimento de hipotermia 12,17,18 .…”
Section: Discussionunclassified
“…A hipotermia no peroperatório é decorrente dos efeitos da anestesia que parecem modificar a temperatura corpórea pela alteração intrínseca dos mecanismos termorreguladores do hipotálamo associados a uma série de outros fatores como a temperatura da sala cirúrgica, a ventilação prolongada com gases secos, a infusão de líquidos frios e a exposição da cavidade abdominal 12, [14][15][16] .…”
Section: Gráfico 2 -Médias Da Temperatura Retal Por Grupo E Momentounclassified
“…Endtidal CO 2 monitors may also be used, as most patients will be endotracheally intubated. Pneumoperitoneum with carbon dioxide likely contributes to intraoperative hypothermia [ 65 ]. Therefore, patients should routinely be covered with upper-body forced-air heating devices to maintain normothermia.…”
Section: Patient Monitoringmentioning
confidence: 99%